User Satisfaction with Computer-Based Test (CBT): The Mediating Role of CBT Centre Service Satisfaction - Hassan Bello; Nor Athiyah Abdullah (Interaction Design and Architecture(s), 2022)
User satisfaction with most goods and services in the information system (IS) has been well studied. However, there appears to be little research on examinees' satisfaction with facilities and services provided at computer-based test (CBT) centres, particularly when the centres are equipped and manned by outsourced vendors. In Nigeria, the CBT centres are public and private examination centres equipped to conduct the annual matriculation examination computer-based test. The study aims to investigate and empirically test the role of quality factors in predicting CBT satisfaction. The study also intends to test a mediator to explore further how some quality factors influence the examinee's satisfaction. The research framework is based on the updated information system success model (ISSM) and is validated using a survey incorporating system quality, service quality, question content, the cost-effectiveness of CBT services, and CBT centre service satisfaction. A total of 455 surveys using structural equation modelling were analysed.